(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This paper proposes a detailed study of the implications of a treatise on choirs attributed to Sophocles. In this lost work, the focus was on choral activity, understood through the confrontation between tradition and its renewal. Based on the indirect references to Sophocles’ career and dramaturgy found in authors and works from antiquity, the aim was to make understandable the performative contexts that best clarify Sophocles’ possible ideas and arguments.